CRISPR interference (CRISPRi) for gene regulation and succinate production in cyanobacterium S. elongatus PCC 7942. Issue 1 (December 2016) - Huang, Chun-Hung; Shen, Claire; Li, Hung; Sung, Li-Yu; Wu, Meng-Ying; Hu, Yu-Chen
Abstract Background CyanobacteriumSynechococcus elongatus PCC 7942 holds promise for biochemical conversion, but gene deletion in PCC 7942 is time-consuming and may be lethal to cells. CRISPR interference (CRISPRi) is an emerging technology that exploits the catalytically inactive Cas9 (dCas9) and single guide RNA (sgRNA) to repress sequence-specific genes without the need of gene knockout, and is repurposed to rewire metabolic networks in various procaryotic cells. Results To employ CRISPRi for the manipulation of gene network in PCC 7942, we integrated the cassettes expressing enhanced yellow fluorescent protein (EYFP), dCas9 and sgRNA targeting different regions oneyfp into the PCC 7942 chromosome. Co-expression of dCas9 and sgRNA conferred effective and stable suppression of EYFP production at efficiencies exceeding 99%, without impairing cell growth. We next integrated the dCas9 and sgRNA targeting endogenous genes essential for glycogen accumulation (glgc ) and succinate conversion to fumarate (sdhA andsdh B). Transcription levels ofglgc, sdhA andsdh B were effectively suppressed with efficiencies depending on the sgRNA binding site. Targeted suppression ofglgc reduced the expression to 6.2%, attenuated the glycogen accumulation to 4.8% and significantly enhanced the succinate titer. TargetingsdhA orsdhB also effectively downregulated the gene expression and enhanced the succinate titer ≈12.5-fold to ≈0.58–0.63 mg/L. Conclusions These data demonstrated that CRISPRi-mediated gene suppression allowed for re-directing the cellular carbon flow, thus paving a new avenue to rationally fine-tune the metabolic pathways in PCC 7942 for the production of biotechnological products.